Ammonium in solution of flooded West African soils - Narteh, L.T.; Sahrawat, K.L. (Elsevier, 2000)
Ammonium production is the key process for N nutrition of lowland rice because the mineralization process stops at ammonium in submerged soils. We studied the changes in ammonium N in the solution of 15 diverse wetland West African soils. Soil samples were held under flooded conditions in the greenhouse pots for 15 weeks, and anoxic solutions, drawn weekly, were monitored for the changes in ammonium N concentrations. The soils differed in the pattern of ammonium accumulation, and had a wide range of ammonium N mobilized in soil solution with mean values ranging from 0.3 to 7.4 mg N kg−1 soil. Ammonium N released in solution was related to organic C and total N contents of the soils. The pattern of ammonium N release in solution of the 15 soils, with the exception of two soils, was well-described by an exponential model. The fit to the linear log model was also good for most of the soils but the prediction was less consistent than with the exponential model. Our results indicate that the pattern of ammonium accumulation in soil solution of flooded West African soils can be described by an exponential model.